Representation Of Toxic Positivity In Clash Of Champions Shows On The Ruangguru Youtube Channel (Case Study at SMA Negeri 1 Tumijajar) - Armita Sahrul; Wawan Hernawan; M. Denu Poyo (Cita konsultindo, 2025)
This study aims to analyze the representation of toxic positivity in the Clash of Champions broadcast on the Ruangguru YouTube Channel (Case Study at SMA Negeri 1 Tumijajar). The research method used was qualitative with a descriptive approach. Data were collected through interviews, observations, and documentation with students at SMA Negeri 1 Tumijajar. The data were analyzed using qualitative descriptive analysis. The results show a representation of toxic positivity. According to students of SMA Negeri 1 Tumijajar, the message that appears in the Clash of Champions broadcast on the Ruangguru YouTube channel is manifested through a narrative that emphasizes the importance of always thinking positively, not giving up, and continuing to fight without a balanced depiction of emotional realities such as sadness, failure, or fatigue. The broadcast tends to simplify the process of achieving success, as if it only requires passion and motivation, without considering social, psychological, or economic obstacles. The meaning contained behind the narrative and visuals of the broadcast Clash of Champions represents toxic positivity in the form of pressure to always appear strong, cheerful, and never give up under any circumstances. According to some students, these messages can be uplifting, but can also be burdensome when under pressure, because they feel they are not allowed to show vulnerability or failure. The consistent visuals of success and happiness reinforce the construct that negative emotions are a form of weakness that must be avoided. The responses of students at SMA Negeri 1 Tumijajar to the representation of toxic positivity in the Clash of Champions show varied. Some students accepted the motivational messages as constructive (dominant-hegemonic), others interpreted them critically (negotiated), and still others felt the messages actually created emotional pressure (oppositional)